Development of Visual Perception Assessment in the Form of an Interactive Digital Book for Students with Mental Disabilities - Yuniarti, Neny; Junaidi, Ahsan Romadlon; Sunandar, Asep (Journal of ICSAR, 2023)
Children with special needs will achieve good learning outcomes if educators conduct assessments.  Assessment is a process to collect information about abilities, advantages and needs that will be used as considerations and decisions related to the preparation of academic programs.  This study aims to develop a visual perception assessment product in the form of a digital book for students with intellectual disability which is expected to be able to measure the ability, difficulty and needs in aspects of the development of children's visual perception with cases of mental impairment needed as consideration in planning learning programs, especially in reading learning.  The method used in this study adapts the Research and Development method initiated by Borg & Gall. The validity of the resulting product is calculated by Aiken's V formula which compared with the table r value (0.78) obtained a material validity value of 0.95 (very valid), a media validity of 0.90 (very valid) and a system validity of 0.91(very valid). The reliability of the products developed proved to be reliable and consistent based on the Cronbach Alpha test which obtained a value of 0.744, higher than the minimum Cronbach Alpha score limit of 0.60. The implementation of the assessment by students with mental disabilities obtained a score of 96.9 percent, meaning that the product can be used very well. Based on the results of this study, the visual perception assessment in the form of interactive digital books for students with intellectual disability that have been developed is suitable for use.